Upper Limb Amputations Following Electric Burn: Experience Sharing from Tertiary Hospitals in Bangladesh - Begum, Nurunnahar; Ahmed, Tanveer; Moni, Zahangir Alom; Kalam, Md Abul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: High voltage electrical burn is one of the most devastating burn injuries involving upper limbs in Bangladesh. It causes serious disfigurement and may lead to loss of the whole upper limb. The aim of this study was to see the severity of electric burn injury involving upper limbs pausing amputations at different levels in two tertiary level referral hospitals of Bangladesh. Methods: A prospective observational study was designed to collect the data from Burn and Plastic Surgery Unit, Dhaka Medical College Hospital and Sheikh Hasina National Institute of Burn and Plastic Surgery from January 2019 to December 2019. One hundred and sixty-nine (169) patients with high voltage electrical burn injury involving upper limb underwent amputation were analyzed according to the severity based on clinical assessment. Results: Male predominance (89%) was observed where right upper limb was involved in 49% of the cases and in 11% cases amputation was bilateral. The most alarming finding was 57.4% patients were below the age of 21 years. Below elbow amputation was done in 48.5% cases followed by above elbow amputations in 32.54% cases. Conclusion: Male sex and younger age are the two most common association with electric burn and subsequent limb amputation. The incidence in higher in upper limbs. This study will help us to create the awareness and for prevention of electric burn. J Bangladesh Coll Phys Surg 2022; 40: 279-286